Pharmacokinetics and safety of single and multiple doses of rasagiline in healthy Japanese and caucasian subjects. Issue 3 (21st October 2018) - Elgart, Anna; Rabinovich‐Guilatt, Laura; Eyal, Eli; Gross, Aviva; Spiegelstein, Ofer
Abstract: As of March 2018, rasagiline is approved for the treatment of Parkinson disease in 55 countries including Japan. The present study evaluated the pharmacokinetics (PK) and safety of rasagiline in healthy Japanese and Caucasian subjects following single and multiple administrations of three rasagiline doses. In this double‐blind, placebo‐controlled study, 64 healthy subjects (32 Japanese and 32 Caucasian) received either rasagiline (0.5, 1.0, or 2.0 mg) or placebo for 10 days with PK sampling for single‐dose administration on day 1 and for multiple administration on day 10. Regardless of administration schedule, rasagiline plasma concentrations and dose‐related increases in exposure parameters were similar between Japanese and Caucasians. Rasagiline accumulation (2‐fold for 0.5 mg and 3‐fold for 1.0 mg and 2.0 mg doses) following multiple administration was similar across the ethnic groups. Geometric mean ratios (GMR) comparing Japanese to Caucasians for AUC0‐24, C max and AUCinf following single administration were 1.38, 1.17 and 1.38 for 0.5 mg; 1.22, 1.20 and 1.22 at 1.0 mg; and 1.02, 1.00 and 1.02 at for 2.0 mg. GMR for AUCtau and C max, ss following multiple administration were 1.43 and 1.06 at 0.5 mg, 1.06 and 1.00 at 1.0 mg, and 1.09 and 1.07 at 2.0 mg. Safety measures were unremarkable and similar between Caucasian and Japanese subjects. Comparable systemic exposure and safety parameters were demonstrated for rasagiline administered to healthy Japanese and Caucasian subjects.